2013
DOI: 10.5664/jcsm.2342
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Characteristics of the Pittsburgh Sleep Quality Index in English Speaking Non-Hispanic Whites and English and Spanish Speaking Hispanics of Mexican Descent

Abstract: Across groups, a 3-factor model of the PSQI more reliably assessed sleep quality than a single-factor global score. Results indicate that the 3-factor structure of the PSQI was uniform across English speaking NHW and English and Spanish speaking HMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
44
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 32 publications
(38 reference statements)
7
44
2
1
Order By: Relevance
“…The samples represented a variety of clinical disorders, including cancer [35,36,50,72], schizophrenia, and chronic fatigue syndrome [63,68], as well as healthy participants of varying ages [40,41,49,51], sexes [46e80], and races and ethnicities [49,78].…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The samples represented a variety of clinical disorders, including cancer [35,36,50,72], schizophrenia, and chronic fatigue syndrome [63,68], as well as healthy participants of varying ages [40,41,49,51], sexes [46e80], and races and ethnicities [49,78].…”
Section: Search Resultsmentioning
confidence: 99%
“…Four studies [48,55,62,78] using factor analysis reported low factor loading for the SM sub-scale and another reported low factor loading for the DD sub-scale [70]. The authors reported that improved fit statistics could be obtained after removal of these items.…”
Section: Factor Structurementioning
confidence: 90%
See 1 more Smart Citation
“…Factor analytical studies of the PSQI have mostly found a single factor although some studies have reported a three factor model [12][13][14][15]. In many studies ''use of sleep medications'' did not load well into the one factor model.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep quality was measured with the 3-factor version of the Pittsburgh Sleep Quality Index (PSQI), which assesses sleep quality during a 1-mo period (40,41). As validated by Tomfohr et al (40), we used 6 of the 7 PSQI subscales (Subjective Sleep Quality, Sleep Duration, Sleep Disturbance, Sleep Efficiency, Daytime Dysfunction, and Sleep Latency).…”
Section: Anxiety Symptoms the Validated Spanish Version Of The Patiementioning
confidence: 99%